Republic of Mozambique : Ex Post Assessment of Mozambique's Performance Under Fund-Supported Programs. (IMF Staff Country Reports; Country Report ;, 2004)
Main objectives of this paper are to assess Mozambique's progress in implementing its program of economic reform under IMF-supported programs since 1987, and to draw lessons for a possible successor arrangement. Four IMF-supported programs were carried out in Mozambique during the period 1987-03. The main developments under IMF-supported programs and evaluation of the country's performance are described. The study focused on aid effectiveness and also discussed the possible continuation of IMF support. A chronology of main policy measures adopted are also presented in detail.